Pengembangan Media Pembelajaran Interaktif Berbasis Audio Visual Menggunakan Canva pada Pelajaran Sistem Komputer untuk Siswa Kelas VII di SMP Islam Al Fattahiyyah - Mohammad Aziz Setya Kusuma; Fahrur Rozy (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
Low student motivation and learning outcomes in the Computer Systems subject at SMP Islam Al Fattahiyyah have become a major issue that needs to be addressed. This study aimed to develop interactive audio-visual learning media using Canva to create a more engaging and effective learning experience. The research employed a Research and Development (R&D) method with the ADDIE development model, which includes needs analysis, media design, product development, implementation through small and large group trials, and feasibility evaluation. The instruments used comprised interview guidelines, student needs questionnaires, expert validation sheets, and student response questionnaires. Validation results showed feasibility scores of 88.8% in the first media expert assessment, 92% in the second, 81.6% from another media expert, and 92.94% from the material expert. The small group trial reached 86.125%, and the large group trial achieved 84%, with an overall average of 88.76%, categorized as highly feasible. These findings indicate that interactive learning media based on Canva are effective in improving student motivation and understanding of computer systems material.